ADHD as an executive dysfunction - Zorcec, T; Pop-Jordanova, N (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2010)
Attention-deficit/hyperactivity disorder [ADHD] is a neuropsychiatric disorder characterized by inattention, hyperactivity and impulsivity that affects from 3-5% of school-aged children. In some cases it may persist into adulthood. Prominent theories about ADHD suggest that inattention, hyperactivity and impulsivity may be due to underlying deficits of the components of attention, including alerting, orienting and executive control. The aim of this study was to investigate neuropsychological characteristics of ADHD children, especially their executive functions [EFs]. The sample is comprised of 30 ADHD children from 6 to 14 years old [10, 45±22, 2], only boys, diagnosed at the department of psychophysiology, University Children's Hospital. The diagnosis was established according to ICD-10 criteria. All children had an IQ over 90 and were medication free. Psychological assessment of the children was performed with the Wechsler Intelligence Scale for Children [WISC-IV] and ADD-H Comprehensive Parent Rating Scale [ASTeRS]. Neuropsychological assessment was performed with the Stroop test and the Wisconsin Card Sorting Test [WCST]. Results showed an average IQ, manifested symptoms of hyperactivity and executive dysfunction, confirmed by the Stroop test and WCST.